The Effect of Leverage, Good Corporate Governance and Company Growth on Earnings Management with Company Size as an Intervening Variable - Mulyadi, Olandari (UPI YPTK Journal of Business and Economics, 2024)
This research aims to analyze the extent of the influence of Leverage, Good Corporate Governance and Company Growth on Earnings Management with Company Size as an Intervening Variable. This research uses quantitative methods. With a research data population of 210 manufacturing companies listed on the Indonesia Stock Exchange per year, using purposive sampling techniques a sample of 290 companies was obtained during the 2017-2021 period. Data were analyzed using SPSS version 25. The results of the analysis show that: (1) Leverage partially influences company size. (2) Good Corporate Governance partially influences company size. (3) Partial company growth has no effect on company size. (4) Leverage partially influences Earnings Management. (5) Good Corporate Governance partially influences Earnings Management. (6) Company growth does not partially affect Earnings Management. (7) Company size partially has no effect on Earnings Management. (8) There is no direct influence between Leverage on Earnings Management through Company Size as an intervening variable. (9) There is a direct influence between Good Corporate Governance on Earnings Management through Company Size as an intervening variable. (10) There is no direct influence between Company Growth on Earnings Management through Company Size as an intervening variable.